Women’s knowledge, attitude, and practice regarding cervical precancerous lesions: a cross-sectional study in Beijing, China - Wang, Lingyan; Wang, Qianping; Zhou, Xia; Liu, Huan (Frontiers in Public Health, 2024)
Background: This study aimed to examine the knowledge, attitude, and practice (KAP) of women in Beijing regarding cervical precancerous lesions. Methods: This web-based, cross-sectional study included women at Dongzhimen Hospital of Beijing University of Chinese Medicine between March 13, 2024 and April 9, 2024. A self-administered questionnaire was developed to collect participants’ demographic information and KAP scores toward cervical precancerous lesions. Results: The study included 951 valid questionnaires, with a mean age of 40.0 years. The mean knowledge, attitude, and practice scores were 12.55±6.23 (possible range: 0-26), 50.66±7.48 (possible range: 13-65), and 26.13±4.98 (possible range: 7-35), respectively. The knowledge score (OR=1.071, 95%CI: 1.040-1.103, P<0.001), currently married (OR=0.548, 95%CI: 0.304-0.985, P=0.045), and with a history of HPV infection (OR=2.302, 95%CI: 1.062-4.990, P=0.035) were independently associated with the attitude score. The knowledge score (OR=1.155, 95%CI: 1.119-1.192, P<0.001), monthly income >20,000 (OR=2.793, 95%CI: 1.249-6.248, P=0.012), a history of HPV infection (OR=0.380, 95%CI: 0.222-0.650, P<0.001), unknown HPV infection status (OR=0.289, OR=0.177-0.473, P<0.001), vaccinated against HPV (OR=1.752, 95%CI: 1.221-2.514, P=0.002), giving birth to one child (OR=1.991, 95%CI: 1.186-3.341, P=0.009), and giving birth to two or more children (OR=2.160, 95%CI: 1.240-3.763, P=0.007) were independently associated with the practice score. The structured equation model showed that knowledge directly influenced attitude (β=0.237, P=0.004) and practice (β=0.490, P=0.010). Attitude directly influenced practice (β=0.193, P=0.009). Conclusion: This study revealed inadequate knowledge, moderate attitude, and practice toward cervical precancerous lesions among women in Beijing. Educational interventions should be developed to enhance knowledge in this regard.